Pendekatan penilaian kawasan sensitif alam sekitar menggunakan analisis multi-kriteria - Ahris Yaakup; Foziah Johar; Siti Zalina Abu Bakar; Haibenarisal Bajuri (Environmental Management Society, Malaysia, 2006)
Physical, socio-economic and environmental sustainability are the most important basis in preparing development plans. The assessment of environmentally sensitive areas (ESA) becomes an important agenda following rapid urban development, industrialisation and economic growth which lead to adverse impacts on the environment. Many methods of analysis have been adopted in the assessment of environmentally sensitive areas (ESA) subject to the needs and the study areas. This paper introduces the multi-criteria method as an approach in the assessment of ESA, and in the formation of a development scenario that can determine the best alternative for a development plan. The multi-criteria method emphasises subjective transparency and judgement in the selection of sets of alternatives that affects the interests of stakeholders and decision-makers. The integration of information technology into the planning process using Geographical Information System (GIS) with the capability of utilising and manipulating spatial and non-spatial data results in better and more rational planning decisions. Database development and spatial modelling provide new dimensions in the analysis, in the painting of current scenario, and in achieving better data presentation in the process of determining ESA